Causal relationships between circulating inflammatory factors and IgA vasculitis: a bidirectional Mendelian randomization study - Qin, Jiading; Zhang, Ling; Ke, Bo; Liu, Tingting; Kong, Chunfang; Jin, Chenghao (Frontiers in Immunology, 2023)
Background: IgA vasculitis (IgAV) is an immune-associated vasculitis, yet its exact etiology remains unclear. Here, we explore the interaction between IgAV and inflammatory factors using bidirectional Mendelian randomization (MR). Methods: We conducted a bidirectional summary-level MR analysis to delineate the causality of C-reactive protein (CRP), procalcitonin (PCT), and 41 circulating inflammatory regulators with IgAV. Data on genetic variants related to inflammation were obtained from three genome-wide association studies (GWASs) on CRP, PCT, and human cytokines, whereas data on IgAV was from large meta-analyses of GWAS among 216 569 FinnGen Biobank participants. The primary MR analysis was performed using the inverse-variance weighted (IVW) approach, and the sensitivity analyses were carried out using MR-Egger, weighted median, weighted mode, and MR-pleiotropy residual sum and outlier. Results: This study revealed the association of CRP higher levels with increased risk of IgAV through IVW method (Estimate odds ratio [OR] = 1.41, 95% confidence interval [CI]: 1.01-1.98, P = 0.04), MR-Egger (OR = 1.87, CI: 1.15-3.02, P = 0.01), weighted median (OR = 2.00, CI: 1.21-3.30, P = 0.01) and weighted mode (OR = 1.74, CI: 1.13-2.68, P = 0.02). Furthermore, elevated IL-8 was strongly implicated with a higher risk of IgAV (IVW OR = 1.42, CI: 1.05-1.92; P = 0.02). Conversely, genetically predicted IgAV was associated with decreased levels of TNF-β (IVW estimate β = -0.093, CI: -0.178 - -0.007; P = 0.033). Additionally, no such significant statistical differences for other inflammatory factors were found. Conclusion: Our current study using bidirectional MR analysis provides compelling evidence for a causal effect of CRP, PCT, and circulating inflammatory regulators on IgAV. These findings contribute to a better understanding of the pathogenesis of IgAV and emphasize the potential of targeting inflammatory factors for therapeutic interventions.